2020
DOI: 10.1111/cns.13542
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of spinal ASIC1 by miR‐485 mediates enterodynia in adult offspring rats with prenatal maternal stress

Abstract: Aims Irritable bowel syndrome (IBS) is a common functional gastrointestinal disease characterized by abdominal pain. Our recent study has shown that the acid‐sensitive ion channel 1 (ASIC1) in dorsal root ganglion (DRG) is involved in stomachache of adult offspring rats subjected with prenatal maternal stress (PMS). MiR‐485 is predicted to target the expression of ASIC1. The aim of the present study was designed to determine whether miR‐485/ASIC1 signaling participates in enterodynia in the spinal dorsal horn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
3
0
1
Order By: Relevance
“…Consistent with previous studies, 4,5,30 chronic visceral hypersensitivity was successfully induced in PMS offspring rats that were 6, 8 and 10 weeks of age, but no difference was observed in 4‐week‐old PMS rats when compared with CON rats (Figure 1B , n = 6 rats for each group, compared with CON group, ** p < 0.01, *** p < 0.001, Tukey's post hoc test following two‐way ANOVA). The expression of GRK6 mRNA in ACC of 6‐week‐old PMS rats was detected by qPCR.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies, 4,5,30 chronic visceral hypersensitivity was successfully induced in PMS offspring rats that were 6, 8 and 10 weeks of age, but no difference was observed in 4‐week‐old PMS rats when compared with CON rats (Figure 1B , n = 6 rats for each group, compared with CON group, ** p < 0.01, *** p < 0.001, Tukey's post hoc test following two‐way ANOVA). The expression of GRK6 mRNA in ACC of 6‐week‐old PMS rats was detected by qPCR.…”
Section: Resultssupporting
confidence: 90%
“…Studies have reported that VH is a stress-sensitive disorder of brain-gut interactions associated with a higher prevalence of adverse early life-forming events. 3 We have previously reported that offspring rats with prenatal maternal stress (PMS) were afflicted with IBS-like visceral pain, 4,5 but the central mechanism of visceral hypersensitivity (VH) in PMS rats remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Интересными представляются данные о том, что на риск возникновения СРК может влиять и психоэмоциональное состояние матери в период беременности [44]. В эксперименте пренатальный материнский стресс приводил к висцеральной гиперчувствительности и абдоминальной боли у потомства опосредованно путем повышения экспрессии цистатионин-β-синтазы и нейротрофического фактора в спинном мозге [45], а также за счет усиления передачи болевых сигналов в дорсальном роге спинного мозга в результате снижения экспрессии miR-485 и увеличения количества кислоточувствительных ионных каналов ASIC1 [46]. В клиническом исследовании J. Galley и соавт.…”
Section: психологические факторыunclassified
“…Furthermore, a rat study has shown that prenatal maternal stress can lead to visceral hypersensitivity in the offspring, and this change may be mediated by the upregulation of cystathionine-β-synthase and Nav1.7 expression. Animal studies have also reported that miR-485/ASIC1 signaling and BDNF expression are associated with the occurrence of visceral hypersensitivity in offspring following prenatal stress ( 60 , 61 ). Therefore, stress during pregnancy could also increase the risk of offspring developing IBS through a mechanism of visceral hypersensitivity ( 62 ).…”
Section: Adverse Exposures In Early Life and Ibsmentioning
confidence: 99%